The composition analysis of coal-derived light oil - 高振楠 刘立麟 朱肖曼 李文博 (Journal of coal science & engineering, China, 2008)
The composition of coal-derived light oil （IBP-220 ℃） was separated into 5 fractions by atmospheric distillation and analyzed by gas chromatography/mass spectrometry （GC/MS）. The light oil was made at 0.1 t/d coal direct liquefaction bench scale unit （BSU） at China Coal Research Institute （CCRI）. Six groups of organics, including acyclic hydrocarbon, alicyclic hydrocarbon, aromatics, phenols, polynuclear aromatics and heterocyclics, were found and 80 compounds were tentatively identified in total. Alicyclic hydrocarbon is the main component of the light oil compared to other groups whether in relative mass percentage or the number of compounds in group. The predominant oxygen-contained compound is phenols, and the nitrogen-containing compound is pyridine. No sulfur-containing compound is detected.